An Application of Geographic Information System to Identify the Suitability of Sea Cucumbers (Holothuria scabra) in West Lombok Waters - Mulyani, Laily Fitriani; Marsoedi, Marsoedi; Guntur, Guntur (Graduate School, Universitas Brawijaya, 2017)
This study was conducted on 17th October - 27th November 2016 at Gili Asahan, Gili Layar, and Gili Gede in West Sekotong, Lombok, West Nusa Tenggara. The purpose of this study was to analyze a suitable area for sea cucumber (Holothuria scabra) cultivation. Data collection had been done by survey method, acquiring primer and secondary data directly related to sea cucumber's life and analyzed by using ArcGIS software. A biological parameter for completing data of West Lombok Waters consisted of sandy mud, rocks, sand and rubble, chlorophyll-a 0.15-0.27 mg.m-3, and biomass cucumbers of 1-7 individuals. Land suitability classes were determined by the class interval, namely, S1 (27-33), S2 (20-26) and N (13-19). Based on the results of scoring that has been adapted to the class interval, this project obtained sample points with a very suitable category (S1), namely, A1, A2, A3, B3, C1, C2, C3. For the corresponding category (S2), there were C4 and C5.Finally, unreliable categories have been found in sample points B1 and B2.Keywords: GIS, Land Suitability, Sea Cucumber, West Lombok Waters.